Technological Progress in the Models of Economic Growth Using Panel Data: Some New Assessments and Empirical Evidence from BRICS-T Countries - Yağmur, Ayten; MANGIR, Fatih; Ertuğrul, Hasan Murat (International Journal of Contemporary Economics and Administrative Sciences, 2022)
Considering the recent growth pattern of the digital world, this paper investigates the impact of technological progress on economic growth based on endogenous technological change models by using patent applications, mobile phone and internet users, research, and development expenditures as an independent variable to economic growth in BRICS-T countries from 2004 to 2018. Panel data set with various tests is used to provide the relationship between the dependent variable (economic growth) and independent variables for these countries. The existence of long-run relationship between economic growth and technological variables concludes that technology usage has significant and positive impact on economic growth in the long term. And it reveals the motivation for governments to adopt specific policies by accelerating investments against the productivity paradox. Based on these empirical findings, further policy implications for economic growth and technological development are discussed.